Corruption, marketisation and corporate tax management in China: Evidence from listed firms - Zhang, C.; Cheong, K.C.; Rasiah, R. (Malaysian Economic Association, 2017)
Most empirical research on the subject of tax management has emphasised the impact of internal corporate governance. Yet, the external governance mechanism regulating corporate behaviour is no less important, but far less studied. This study investigates how corruption and marketisation impact corporate tax management, which lowers corporate tax. It finds an inverted U-shape relationship between corruption and corporate tax management in China during the period of 2008 to 2013, with the effect positive at low to moderate levels of corruption and negative beyond these levels of corruption. However, marketisation, i.e., the greater reliance on market forces, is found to mitigate this impact of corruption on corporate tax management regardless of the level of corruption. In light of these findings, greater reliance on market institutions will directly and indirectly improve corporate decision making.